Models for operational risk management in the investment firms in the European integration process of the Republic of Serbia - Sovilj Ranko; Stojković-Zlatanović Sanja (Megatrend Revija, 2018)
As a response to the financial crisis that hit the world in 2007, European Parliament adopted a number of international regulations that focus on improving the ability of the financial sector to absorb the losses arising from the economic and financial stress. Additionally, the aim is to reduce the risk of the financial sector crisis affecting the real economy. The author highlights the necessity and importance of offering new solutions, proposed by Basel III standards and EU directives. The proposed solutions, as a general model of operational risk management in the investment companies, are based on qualitative and quantitative aspects. They should help the investment firms survive in the capital markets and encourage their further development and competitiveness on the global capital markets. Hence, this paper points out the importance of early detection and the identification of operational risks in the investment firms, as well as the development of different models of operational risk management.